NISC disks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The National Information Services Corporation (NISC) provides CD-ROM databases which cover scientific, practical and information disciplines. The subjects range from aquaculture to worldwide wildlife, combining information from a number of different...